Guerre et récit chez les Indiens ayorés du Chaco boréal paraguayen - Salvatore D’Onofrio (Journal de la Société des Américanistes)
Warfare and Story among the Ayoreo Indians of the Paraguayan Chaco. For the Ayoreo Indians of the Paraguayan Chaco, warfare is not something just to be fought, it is also something to be recounted in stories. The right to tell the story belongs in principle only to those who have already killed. This sort of pantomime, little known among other Indians of the lowlands, is related to myth by virtue of the canonical manner in which it unfolds and of the connexions it establishes with other aspects of Ayoreo culture: body painting, hunting, shamanic powers, ritual activities. Ayoreo warfare – compelled in order to be effective to inscribe itself within a symbolic horizon – is modelled on the basis of the logic of predation, as has been emphasized in several recent works, but confirms – above all through the analysis of substances and gestures – its possible conversion into an exchange relationship.